2009
DOI: 10.1074/jbc.m805550200
|View full text |Cite
|
Sign up to set email alerts
|

Cell Entry of Arginine-rich Peptides Is Independent of Endocytosis

Abstract: Arginine-rich peptides are a subclass of cell-penetrating peptides that are taken up by living cells and can be detected freely diffusing inside the cytoplasm and nucleoplasm. This phenomenon has been attributed to either an endocytic mode of uptake and a subsequent release from vesicles or to direct membrane penetration (transduction). To distinguish between both possibilities, we have blocked endocytic pathways suggested to be involved in uptake of cell-penetrating peptides. We have then monitored by confoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
175
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(187 citation statements)
references
References 54 publications
9
175
1
2
Order By: Relevance
“…S7). The kinetic profile also revealed an initial lag time for membrane adsorption and subsequent cellular internalization, which agrees with other studies showing that Tat enters cells using endocytic routes [32][33][34][35]. In Table 1.…”
Section: Deciphering the Kinetics Of Cpp Cellular Entry By Rt-facssupporting
confidence: 90%
“…S7). The kinetic profile also revealed an initial lag time for membrane adsorption and subsequent cellular internalization, which agrees with other studies showing that Tat enters cells using endocytic routes [32][33][34][35]. In Table 1.…”
Section: Deciphering the Kinetics Of Cpp Cellular Entry By Rt-facssupporting
confidence: 90%
“…In light of this, recent reports excluding endocytosis as an uptake mechanism do not appear convincing. [79] Since passive membrane diffusion of peptides has long been known as impossible, [80,81] what else can possibly be offered as a transport mechanism? Transient water wires across a lipid bilayer.…”
Section: Discussionmentioning
confidence: 99%
“…The diffuse staining was not due to the release of peptide from endosomes as it appeared first and the punctate staining later, and it continued to occur at 4°C when endocytosis is inhibited. Several other studies have also reported cellular uptake when the cells have been incubated at 4°C [26,[51][52][53]. It has also been observed that blocking specific endocytotic pathways does not affect the ability of TAT peptide to enter cells.…”
Section: Direct Translocation Endocytosis: An Either/or Discourse?mentioning
confidence: 91%
“…The TAT protein is an 86 amino acid long protein that is released by infected cells and is an essential regulatory gene for HIV replication [8]. In 1997, Vives et al [9] found that a 11-amino acid sequence, TAT (47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57), now known as the TAT peptide or TAT PTD, can not only enter cells but is more efficient than the full length protein. It was observed that the chirality of the peptide backbone has no effect on cellular uptake of TAT peptide; inverse and retro forms were able to enter cells as efficiently as the native peptide, suggesting uptake does not require a specific binding site.…”
Section: Tat As a Prototypical Example Of A Cell-penetrating Peptidementioning
confidence: 99%